Lamotrigine versus inert placebo in the treatment of borderline personality disorder: study protocol for a randomized controlled trial and economic evaluation - Crawford, Mike J.; Sanatinia, Rahil; Barrett, Barbara; Byford, Sarah; Cunningham, Gillian; Gakhal, Kavi; Lawrence-Smith, Geof; Leeson, Verity; Lemonsky, Fenella; Lykomitrou, Georgia; Montgomery, Alan; Morriss, Richard K.; et al. (BioMed Central, 2015)
Background: People with borderline personality disorder (BPD) experience rapid and distressing changes in mood, poor social functioning and have high rates of suicidal behaviour. Several small scale studies suggest that mood stabilizers may produce short-term reductions in symptoms of BPD, but have not been large enough to fully examine clinical and cost-effectiveness. Methods/Design: A two parallel-arm, placebo controlled randomized trial of usual care plus either lamotrigine or an inert placebo for people aged over 18 who are using mental health services and meet diagnostic criteria for BPD. We will exclude people with comorbid bipolar affective disorder or psychosis, those already taking a mood stabilizer, those who speak insufficient English to complete the baseline assessment and women who are pregnant or contemplating becoming pregnant. Those meeting inclusion criteria and provide written informed consent will be randomized to up to 200mg of lamotrigine per day or an inert placebo (up to 400mg if taking combined oral contraceptives).Participants will be randomized via a remote web-based system using permuted stacked blocks stratified by study centre, severity of personality disorder, and level of bipolarity. Follow-up assessments will be conducted by masked researchers 12, 24 weeks, and 52 weeks after randomization. The primary outcome is the Zanarini Rating Scale for Borderline Personality Disorder (ZAN-BPD). The secondary outcomes are depressive symptoms, deliberate self-harm, social functioning, health-related quality of life, resource use and costs, side effects of treatment, adverse events and withdrawal of trial medication due to adverse effects. The main analyses will use intention to treat without imputation of missing data. The economic evaluation will take an NHS/Personal Social Services perspective. A cost-utility analysis will compare differences in total costs and differences in quality of life using QALYs derived from the EQ-5D. Discussion: The evidence base for the use of pharmacological treatments for people with borderline personality disorder is poor. In this trial we will examine the clinical and cost-effectiveness of lamotrigine to assess what if any impact offering this has on peoples’ mental health, social functioning, and use of other medication and other resources.